Implementation of the Water Swing Track Record Project in a Plastic Bottle to Improve Student Competence in Walking Wave Material - Suparjo (IPTPI Surakarta, 2022)
The aims of this study: (1) describe the implementation of the Water Swing Track Record Project in a Plastic Bottle, (2) also describe how large the competence of the walking wave can be achieved. This best practice is an experience for three years carrying out learning in class XI-MIPA material/wave competence by applying the Project based learned (PjBL) method based on literature sources or even the results of previous researchers' research. The implementation or application of the Project based learned (PjBL) method with the Jr Unair Lambotik Project (a project with a track record of water swings in plastic bottles). The research subjects were students of SMA Negeri 1 Sukoharjo class XI. MIPA 2017/2018 academic year, 2018/2019 school year and 2019/2020 school year which the author was capable of. The Jr Unair Lambotik project is a project that tracks water swings in plastic bottles that can form a transverse traveling wave pattern on used newspapers placed underneath. The implementation of the Jr Unair Lambotik Project is carried out in three stages, namely (a) preparation/design, (b) implementation, and (c) reporting. Through the Jr Unair Lambotik Project, product scores, project report scores, and concept scores were obtained. In general, the competence of the walking wave of SMA Negeri 1 Sukoharjo students for the 2018/2019 school year and the 2019/2020 school year can be improved. The achievements of these improvements are respectively as follows for the average value of the results of the Jr Unair Lambotik Project is 88.56 < 88.59, for the average report value of the Jr Unair Lambotik Project is 85.44 < 85.83, and for the average value of the Jr Unair Lambotics project concept which is a competency knowledge of traveling wave material is 73.35 (current wave value for the 2017/2018 academic year) < 75.97 < 76.20.